Psychotherapy and Outcome Research in PTSD: Understanding the Challenges and Complexities in the Literature - Black, Timothy G. (Canadian Journal of Counselling and Psychotherapy, 2007)
The author reviews the existing literature on posttraumatic stress disorder (PTSD, American Psychiatric Association, 2000) as it relates to outcome research and psychotherapy. An initial examination of the issues involved in outcome research includes the issue of assessment and diagnosis, followed by the issue of measurement. The article is meant to assist those counsellors who are interested in the treatment of PTSD and understanding the complexities and challenges involved in determining what works and what does not. The author makes suggestions regarding how to approach the literature on PTSD, as well as issues in treating clients suffering from PTSD.